Resin emulsion dispersion modification process in production of water-based thermal insulation coating
Patent Information
- Application Number
- CN202611508248.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0002]水性隔热涂料是建筑节能和工业储罐热防护中常用的功能涂料,其隔热性能主要取决于涂层中高折射率颜料对太阳光的反射作用,以及中空、多孔微粒形成的隔热结构,在现有涂料制备工艺中,通常将金红石型二氧化钛、煅烧高岭土和中空玻璃微珠等无机功能填料分散在水性丙烯酸酯乳液中形成涂料体系,这些功能填料在水相中的分散是否均匀、与树脂乳液之间的润湿是否充分,会直接影响固化涂膜的太阳光反射比和隔热性能,在实际分散制浆过程中,二氧化钛等高折射率颜料表面能较高,容易发生团聚,需要施加较强的剪切作用,使团聚的颜料充分解聚并达到适于光反射的粒径范围,但是,中空玻璃微珠和多孔气凝胶微粒的抗压强度较低,在高速剪切和颗粒碰撞过程中容易出现壳壁破裂或孔隙坍塌,使其中原有的封闭空气结构受到破坏,进而降低干膜的隔热性能,同时,聚合物乳胶粒子主要依靠双电层和水化膜保持稳定,较强的剪切作用还容易使乳液发生破乳和凝聚,影响后续成膜的致密性
1、在一种水性隔热涂料生产中的树脂乳液分散改性工艺中,通过提高水性丙烯酸酯共聚物乳液在强剪切条件下的稳定性,使金红石型二氧化钛粉体等高折射率颜料能够充分分散,而不会因高速剪切造成乳液破乳;在颜料完成分散后再降低剪切强度加入中空绝热微粒,可减少钠硼硅酸盐中空微珠在搅拌过程中的破损,较完整地保留微珠内部的密闭空气空腔,由此能够兼顾颜料充分解聚和中空微珠完整性,在保持涂层较高光反射能力的同时降低热量传导,改善水性隔热涂料的隔热性能。
Smart Images

Figure CN123004218A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional coating manufacturing technology, and more specifically, to a resin emulsion dispersion modification process in the production of water-based heat insulation coatings. Background Technology
[0002] Waterborne thermal insulation coatings are commonly used functional coatings in building energy conservation and industrial storage tank thermal protection. Their thermal insulation performance mainly depends on the reflection of sunlight by high-refractive-index pigments in the coating, as well as the thermal insulation structure formed by hollow, porous microparticles. In existing coating preparation processes, inorganic functional fillers such as rutile titanium dioxide, calcined kaolin, and hollow glass microspheres are typically dispersed in waterborne acrylic emulsions to form the coating system. The uniformity of dispersion of these functional fillers in the aqueous phase and the sufficient wetting between them and the resin emulsion directly affect the solar reflectance and thermal insulation performance of the cured coating film. In the actual dispersion and slurry preparation process… High-refractive-index pigments such as titanium dioxide have high surface energy and are prone to agglomeration. Strong shearing is required to fully deagglomerate the pigments and bring them to a particle size range suitable for light reflection. However, hollow glass microspheres and porous aerogel microparticles have low compressive strength and are prone to shell wall rupture or pore collapse during high-speed shearing and particle collision, which destroys the original closed air structure and reduces the thermal insulation performance of the dry film. At the same time, polymer latex particles mainly rely on the electric double layer and hydration film to maintain stability. Strong shearing can also easily cause the emulsion to demulsify and coagulate, affecting the compactness of the subsequent film formation.
[0003] If low-shear stirring is used throughout the preparation process, pigment agglomerates are difficult to fully depolymerize, and the hollow microparticles added later are also difficult to be fully wetted and coated by the resin emulsion. After film formation, small pores are easily left between the inorganic filler and the resin. When low molecular weight surfactants are used to improve wetting, free additives may migrate and accumulate on the surface of the paint film during the drying and film formation process, forming hydrophilic capillary channels and reducing the water resistance and washability of the coating. In order to improve the defects of filler blending and waterproofing, existing technologies attempt to make adjustments from the perspective of raw material modification and multi-stage feeding process. For example, Chinese invention patent application with publication number CN113717601A discloses a waterproof reflective heat insulation coating and its preparation method. Titanium dioxide, aerogel and ceramic fiber are pre-dispersed and slurried at high speed, then modified hollow glass microspheres are added and dispersed at a reduced speed, and finally silicone fluorine emulsion is introduced for low-speed blending. In the initial high-speed dispersion stage, the brittle silica aerogel and hard titanium dioxide are subjected to strong shearing, which can easily lead to mechanical damage to the aerogel nanoporous framework.
[0004] Therefore, the technical problem to be solved by this invention is how to reduce the breakage of hollow insulating microparticles during the dispersion process while ensuring sufficient depolymerization of high refractive index pigments, and how to improve the interfacial density between inorganic fillers and resin while reducing the amount of free surfactant. Summary of the Invention
[0005] To address the problems in the background art, the present invention provides a resin emulsion dispersion modification process in the production of water-based thermal insulation coatings, comprising the following steps: Step S1: Add an aqueous phase stabilizer to the aqueous acrylate copolymer emulsion at a speed of 300 rpm to 500 rpm and a temperature of 20°C to 30°C at a dropping rate of 0.5% to 1.0% of the formulation mass fraction per minute, and stir and passivate for 15 min to 25 min to obtain a pre-passivated resin emulsion. Step S2: Add rutile titanium dioxide powder and calcined kaolin micro powder to the pre-passivated resin emulsion, and shear and disperse them online at a speed of 15 m / s to 22 m / s and a temperature not exceeding 45°C for 20 min to 35 min to obtain a semi-coated slurry with an apparent dynamic viscosity of 1200 mPa·s to 2500 mPa·s. Step S3: Reduce the linear velocity to 3 m / s to 6 m / s, add sodium borosilicate hollow microspheres and hydrophobic modified silica aerogel powder to the semi-coated slurry in batches, and homogenize in the semi-coated slurry in laminar flow for 10 min to 20 min. Step S4: A pre-hydrolyzed solution of methacryloyloxypropyltrimethoxysilane is atomized and sprayed into the homogenized material. The reaction is carried out at a temperature of 38°C to 45°C and a pH of 8.2 to 9.0 for 25 min to 40 min, so that the silane hydrolysate and inorganic filler and molecular chain are polycondensed and crosslinked. Step S5: Add an associative polyurethane thickener and a pH adjuster to the reacted material to adjust the pH value to 8.8 to 9.5 and the kinematic viscosity to 85 KU to 110 KU. Cool the material and discharge it through a 200-mesh filter.
[0006] Preferably, based on a total feed weight of 1000 kg, the feed weight of the waterborne acrylic copolymer emulsion is 360.0 kg to 400.0 kg with a solid content of 45 wt% to 55 wt%, the feed weight of the rutile titanium dioxide powder is 150.0 kg to 200.0 kg with an average particle size of 0.19 μm to 0.29 μm, and the feed weight of the calcined kaolin micro powder is 45.0 kg to 55.0 kg. The sodium borosilicate hollow microspheres have a feed mass of 80.0 kg to 90.0 kg, a true density of 0.15 g / cm³ to 0.35 g / cm³, and an isostatic compressive strength of 12 MPa to 18 MPa. The hydrophobically modified silica aerogel powder has a feed mass of 20.0 kg to 30.0 kg and a specific surface area of 600 m² / g to 700 m² / g.
[0007] Preferably, step S1 includes the following sub-steps: step S11, mixing a 40wt% polyether-modified sodium polycarboxylate aqueous solution with a nonionic amphiphilic block copolymer containing polyoxyethylene and polyoxypropylene blocks at a mass ratio of 1:1 to prepare an aqueous phase stabilizer; step S12, adding the aqueous phase stabilizer dropwise to the aqueous acrylate copolymer emulsion at a rotation speed of 300 rpm to 500 rpm.
[0008] Preferably, step S2 includes the following sub-steps: Step S21, controlling the ratio of the outer diameter of the dispersion disc impeller to the inner diameter of the dispersion reactor to be 0.25 to 0.35, circulating cooling water into the jacket of the outer wall of the dispersion reactor to maintain the material temperature in the range of 38°C to 42°C; Step S22, forcefully shearing and dispersing rutile titanium dioxide powder and calcined kaolin micro powder at a dispersion disc linear velocity of 15 m / s to 22 m / s, stopping the high-speed shearing when the slurry dispersion fineness is less than or equal to 20 μm and the hydrodynamic particle size of the rutile titanium dioxide powder is in the range of 0.2 μm to 0.4 μm as detected by a scraper fineness gauge.
[0009] Preferably, step S4 includes the following sub-steps: Step S41, a 15wt% methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution is introduced into an atomization system and sprayed onto the material surface by atomizing spray gun driven by compressed air at a pressure of 0.5MPa, controlling the average atomized droplet size to be 10μm to 30μm; Step S42, the reaction is carried out at a constant temperature of 200rpm to 240rpm and a material temperature of 38℃ to 45℃ for 25min to 40min, so that the covalent bonding coverage of the silane hydrolysis product between the inorganic particle surface and the resin microregion reaches more than 75%.
[0010] Preferably, in step S4, the methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution is injected into a room-temperature latent titanium lactate chelate aqueous solution.
[0011] Preferably, step S3 uses an online torque sensor and a material temperature sensor configured in the dispersion reactor to detect the net torque power output of the dispersion shaft and the material temperature in real time, and includes the following control sub-steps: Step S31, when the apparent dynamic viscosity of the slurry exceeds 2500 mPa·s, the operating speed of the dispersion shaft is reduced to 200 rpm to 250 rpm, and deionized water is injected into the dispersion reactor to bring the apparent dynamic viscosity back to the range of 1200 mPa·s to 2500 mPa·s; Step S32, when the apparent dynamic viscosity of the slurry is lower than 1200 mPa·s, the interval between single batch feedings is extended to 8 min to 12 min to maintain the laminar suspension state of the flow field.
[0012] Preferably, step S5 includes the following sub-steps: step S51, adding a hydrophobically modified ethoxylated urethane copolymer as an associative polyurethane thickener to the reacted material; step S52, adding a pH adjuster to adjust the pH of the system to 8.8 to 9.5.
[0013] Preferably, after the water-based heat-insulating coating prepared by the process is dried, the thermal conductivity of the dry film at room temperature is 0.032 W / (m·K) to 0.038 W / (m·K), the reflectance of the full spectrum of sunlight is greater than or equal to 0.91, the reflectance of the near-infrared spectrum is greater than or equal to 0.93, the hemispherical emissivity is greater than or equal to 0.88, the water absorption rate of the film after immersion in water for 168 hours is less than or equal to 2.5%, and the film can withstand more than 15,000 washes without exposing the substrate.
[0014] The embodiments of the present invention have at least the following beneficial effects: 1. In a resin emulsion dispersion modification process for the production of a waterborne thermal insulation coating, by improving the stability of the waterborne acrylic copolymer emulsion under strong shear conditions, high-refractive-index pigments such as rutile titanium dioxide powder can be fully dispersed without emulsion demulsification caused by high-speed shear. After the pigments are dispersed, hollow thermal insulation microparticles are added to reduce the shear strength, which can reduce the damage of sodium borosilicate hollow microspheres during the stirring process and preserve the closed air cavities inside the microspheres more completely. This can balance the full depolymerization of pigments and the integrity of hollow microspheres, reduce heat conduction while maintaining the high light reflectivity of the coating, and improve the thermal insulation performance of the waterborne thermal insulation coating.
[0015] 2. The pre-hydrolyzed solution of methacryloyloxypropyltrimethoxysilane forms a stronger bond between the inorganic filler and the resin, which can reduce the interfacial gaps caused by insufficient wetting and bonding between the inorganic filler and the resin matrix, making the coating structure more compact. This not only helps to reduce heat transfer at the interface, but also reduces the possibility of moisture and corrosive media penetrating into the coating through the interfacial pores, and improves the coating's adhesion and resistance to humid heat aging.
[0016] 3. By improving the dispersion stability of the emulsion itself and strengthening the bond between inorganic fillers and resin, the system's dependence on free small molecule surfactants can be reduced. This reduces the migration and accumulation of hydrophilic additives on the paint film surface during drying and film formation, as well as the water absorption channels formed therefrom. The resulting coating surface is more continuous and dense, which can reduce the impact of moisture, dust and dirt on the coating. It is also beneficial to maintain the reflective properties of titanium dioxide and thermal insulation fillers, so that the coating can better maintain its solar reflectivity, water resistance and washability during outdoor use. Attached Figure Description
[0017] The above and other objects, features, and advantages of exemplary embodiments of the present invention will become readily apparent from the following detailed description taken in conjunction with the accompanying drawings, in which several embodiments of the invention are illustrated by way of example and not limitation, wherein: Figure 1 This is a flowchart of the resin emulsion fractionation shearing and in-situ modification process of the present invention. Figure 2 This is a diagram showing the phase evolution and interface combination of materials in the dispersion reactor of this invention. Detailed Implementation
[0018] The technical solutions of the present invention will now be described with reference to the accompanying drawings and several exemplary embodiments. It should be understood that these embodiments are provided only to enable those skilled in the art to better understand and implement the present invention, and are not intended to limit the scope of the present invention in any way. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0019] A resin emulsion dispersion modification process in the production of water-based thermal insulation coatings includes the following steps: Step S1: Add an aqueous phase stabilizer to the aqueous acrylate copolymer emulsion at a speed of 300 rpm to 500 rpm and a temperature of 20°C to 30°C at a dropping rate of 0.5% to 1.0% of the formulation mass fraction per minute, and stir and passivate for 15 min to 25 min to obtain a pre-passivated resin emulsion. Step S2: Add rutile titanium dioxide powder and calcined kaolin micro powder to the pre-passivated resin emulsion, and shear and disperse them online at a speed of 15 m / s to 22 m / s and a temperature not exceeding 45°C for 20 min to 35 min to obtain a semi-coated slurry with an apparent dynamic viscosity of 1200 mPa·s to 2500 mPa·s. Step S3: Reduce the linear velocity to 3 m / s to 6 m / s, add sodium borosilicate hollow microspheres and hydrophobic modified silica aerogel powder to the semi-coated slurry in batches, and homogenize in the semi-coated slurry in laminar flow for 10 min to 20 min. Step S4: A pre-hydrolyzed solution of methacryloyloxypropyltrimethoxysilane is atomized and sprayed into the homogenized material. The reaction is carried out at a temperature of 38°C to 45°C and a pH of 8.2 to 9.0 for 25 min to 40 min, so that the silane hydrolysate and inorganic filler and molecular chain are polycondensed and crosslinked. Step S5: Add an associative polyurethane thickener and a pH adjuster to the reacted material to adjust the pH value to 8.8 to 9.5 and the kinematic viscosity to 85 KU to 110 KU. Cool the material and discharge it through a 200-mesh filter.
[0020] Preferably, based on a total feed weight of 1000 kg, the feed weight of the waterborne acrylic copolymer emulsion is 360.0 kg to 400.0 kg with a solid content of 45 wt% to 55 wt%, the feed weight of the rutile titanium dioxide powder is 150.0 kg to 200.0 kg with an average particle size of 0.19 μm to 0.29 μm, and the feed weight of the calcined kaolin micro powder is 45.0 kg to 55.0 kg. The sodium borosilicate hollow microspheres have a feed mass of 80.0 kg to 90.0 kg, a true density of 0.15 g / cm³ to 0.35 g / cm³, and an isostatic compressive strength of 12 MPa to 18 MPa. The hydrophobically modified silica aerogel powder has a feed mass of 20.0 kg to 30.0 kg and a specific surface area of 600 m² / g to 700 m² / g.
[0021] Preferably, step S1 includes the following sub-steps: Step S11, a 40wt% polyether-modified sodium polycarboxylate aqueous solution is compounded with a nonionic amphiphilic block copolymer containing polyoxyethylene and polyoxypropylene blocks at a mass ratio of 1:1 to form an aqueous phase stabilizer; Step S12, the aqueous phase stabilizer is added dropwise to the aqueous acrylate copolymer emulsion at a rotation speed of 300 rpm to 500 rpm, the anionic carboxylate groups coordinate and bind to the surface of the polymer latex particles, and the nonionic polyether segments extend into the aqueous phase to form a steric hydration protective layer with a thickness of 3 nm to 8 nm, thereby increasing the critical demulsification shear rate of the aqueous acrylate copolymer emulsion to more than 12000 / s.
[0022] Preferably, step S2 includes the following sub-steps: Step S21, controlling the ratio of the outer diameter of the dispersion disc impeller to the inner diameter of the dispersion reactor to be 0.25 to 0.35, circulating cooling water into the jacket of the outer wall of the dispersion reactor to maintain the material temperature in the range of 38°C to 42°C; Step S22, forcefully shearing and dispersing rutile titanium dioxide powder and calcined kaolin micro powder at a dispersion disc linear velocity of 15 m / s to 22 m / s, stopping the high-speed shearing when the slurry dispersion fineness is less than or equal to 20 μm and the hydrodynamic particle size of the rutile titanium dioxide powder is in the range of 0.2 μm to 0.4 μm as detected by a scraper fineness gauge.
[0023] Preferably, step S4 includes the following sub-steps: Step S41, a 15wt% methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution is introduced into an atomization system and sprayed onto the material surface by atomizing spray gun driven by compressed air at a pressure of 0.5MPa, controlling the average atomized droplet size to be 10μm to 30μm; Step S42, the reaction is carried out at a constant temperature of 200rpm to 240rpm and a material temperature of 38℃ to 45℃ for 25min to 40min, so that the covalent bonding coverage of the silane hydrolysis product between the inorganic particle surface and the resin microregion reaches more than 75%.
[0024] Preferably, in step S4, a room-temperature latent titanium lactate chelate aqueous solution is injected along with a methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution; the titanium lactate chelate remains chemically inert under room-temperature storage conditions, and when the coating film is heated to above 35°C by photothermal heating, ligand dehydration and dissociation occur, and the released coordinated titanate undergoes a secondary polycondensation and crosslinking reaction with the carboxyl and hydroxyl groups on the polymer molecular chain.
[0025] Preferably, step S3 uses an online torque sensor and a material temperature sensor configured in the dispersion reactor to detect the net torque power output of the dispersion shaft and the material temperature in real time, and includes the following control sub-steps: Step S31, when the apparent dynamic viscosity of the slurry exceeds 2500 mPa·s, the operating speed of the dispersion shaft is reduced to 200 rpm to 250 rpm, and deionized water is injected into the dispersion reactor to bring the apparent dynamic viscosity back to the range of 1200 mPa·s to 2500 mPa·s; Step S32, when the apparent dynamic viscosity of the slurry is lower than 1200 mPa·s, the interval between single batch feedings is extended to 8 min to 12 min to maintain the laminar suspension state of the flow field.
[0026] Preferably, step S5 includes the following sub-steps: Step S51, adding a hydrophobically modified ethoxylated urethane copolymer as an associative polyurethane thickener to the reacted material, whereby hydrophobic association occurs between the hydrophobic end groups and the polymer layer coated on the surface of the inorganic particles, and the hydrophilic polyether segments extend in the aqueous phase to form a three-dimensional network structure; Step S52, adding a pH adjuster to adjust the pH of the system to 8.8 to 9.5, so that the thixotropic yield value of the finished coating under static storage is maintained at a state that prevents the hollow microspheres from floating and hardening, and generates a shear thinning response under the coating shear rate.
[0027] Preferably, after the water-based heat-insulating coating prepared by the process is dried, the thermal conductivity of the dry film at room temperature is 0.032 W / (m·K) to 0.038 W / (m·K), the reflectance of the full spectrum of sunlight is greater than or equal to 0.91, the reflectance of the near-infrared spectrum is greater than or equal to 0.93, the hemispherical emissivity is greater than or equal to 0.88, the water absorption rate of the film after immersion in water for 168 hours is less than or equal to 2.5%, and the film can withstand more than 15,000 washes without exposing the substrate.
[0028] Example 1: In the large-scale production of long-lasting thermal insulation and protective coatings for the outer walls of large petrochemical storage tanks and coastal industrial equipment, there is a contradiction between the sufficient depolymerization of high-refractive-index pigments and the maintenance of the integrity of the sealed thermally insulating cavities of lightweight thermal insulation fillers, and the control of shear speed and dispersion energy. Conventional single shearing processes easily cause the rupture of hollow microsphere shells and the mechanical demulsification of polymer emulsion micelles when applying the strong hydraulic shear required to break up titanium dioxide agglomerates. However, low-speed stirring throughout the process cannot eliminate pigment particle aggregation and lead to phase interface wetting defects. In this example, a staged shear control and in-situ interface reaction process is used to control the material dispersion and reaction state. First, the material is injected into a 1500L dispersion reactor. 165 kg of deionized water and 380 kg of a waterborne acrylic copolymer emulsion with a solid content of 50 wt% and a pH of 7.5 were mixed. A three-bladed low-speed agitator was started and the speed was controlled at 350 rpm. The cooling water circulation in the outer jacket of the reactor was turned on to adjust the material temperature to the range of 22℃ to 25℃. Then, 8 kg of an aqueous phase stabilizer prepared by compounding a nonionic amphiphilic block copolymer containing polyoxyethylene and polyoxypropylene blocks in a mass ratio of 1:1 was added to the emulsion at a dropping rate of 0.8% of the total formula mass per minute. The surface physical adsorption pre-stabilization treatment was carried out for 20 min with continuous stirring. The hydrophobic segments of the nonionic block copolymer polyoxypropylene and the hydrophobic backbone of the sodium polycarboxylate molecule are physically adsorbed and anchored to the surface of acrylate polymer latex particles through hydrophobic association. The hydrophilic polyoxyethylene segments and polyether side chains extend outward into the continuous aqueous phase, constructing a steric hydration protective layer with a thickness of 3 nm to 8 nm on the outer surface of the latex particles. This significantly weakens the tendency of polymer micelles to demulsify and aggregate due to mechanical collisions under strong turbulent shear flow fields, increasing the critical shear rate for demulsification of the aqueous acrylate copolymer emulsion under mechanical shear from 4500 / s without stabilizer to over 12000 / s, thus preparing a pre-polymer with high shear mechanical stability. The passivated resin emulsion provides a rheological and colloidal thermodynamic stability basis for subsequent high-speed, high-force shear dispersion with linear velocities of 15 m / s to 22 m / s. The polyether-modified sodium polycarboxylate used has a weight-average molecular weight of 8,000 to 12,000, a main chain carboxylate neutralization degree of 85% to 95%, and a repeating unit degree of polymerization of the side chain polyethylene glycol monomethyl ether segment of 20 to 35. In the nonionic amphiphilic block copolymer containing polyoxyethylene and polyoxypropylene blocks, the molar ratio of polyoxyethylene segments to polyoxypropylene segments is 4:1 to 6:1, and the weight-average molecular weight is 4,500 to 6,500. The combination of the two can enable the polymer adsorption layer to form a dense spatial hydration repulsion barrier on the surface of latex particles.
[0029] In a pre-passivated resin emulsion, 180 kg of rutile titanium dioxide powder with an average particle size of 0.25 μm and 50 kg of calcined kaolin powder with a particle size of 1.5 μm to 2.5 μm were sequentially added. The ratio of the outer diameter of the dispersion disc impeller to the inner diameter of the dispersion reactor was controlled at 0.30. The high-speed dispersion shaft was started and the linear velocity of the dispersion disc was adjusted to 22.78 m / s. The heat dissipated by the high-shear turbulence was balanced by the cooling water flow rate of the reactor jacket, maintaining the material temperature in the range of 38℃ to 42℃. High-speed, high-intensity shear dispersion was carried out for 30 minutes to achieve the desired effect. Shear stress promotes the complete deagglomeration and dispersion of pigment and filler particles. The fineness of the slurry dispersion, as measured by a scraper fineness gauge, is less than or equal to 20 μm, and the hydrodynamic particle size of the rutile titanium dioxide powder is in the range of 0.2 μm to 0.4 μm. In high-speed turbulent flow, strong fluid shear stress overcomes the intergranular van der Waals forces of the original pigment and filler agglomerates, deagglomerating them and exposing fresh inorganic surfaces. Under the drive of fluid pressure difference and turbulent diffusion, pre-passivated polymer latex particles rapidly migrate, wet, and physically adsorb onto the outer surfaces of the rutile titanium dioxide and calcined kaolin particles, forming a polymer... The solid-liquid suspension phase coated with micelles and hydration films, after depolymerization, exhibits high solids content and fine powder particles. This increases the rheological damping of the continuous phase medium, transforming it into a semi-coated slurry state with an apparent dynamic viscosity ranging from 1200 mPa·s to 2500 mPa·s (measured at 1850 mPa·s). The viscosity damping of this suspension slurry serves two purposes: firstly, it physically isolates the depolymerized pigment particles to prevent secondary anti-agglomeration; secondly, it acts as a fluid buffer medium during homogenization and mixing in subsequent processes to attenuate the instantaneous mechanical impact on the brittle, insulating filler. In actual industrial production operations… The linear velocity of the high-speed dispersion disk is preferably controlled at the standard operating condition reference of 22.0 m / s. For example, when the diameter of the dispersion disk is 0.30 m, the set rotation speed is 1400 rpm, which corresponds to a linear velocity of 22.0 m / s. Under actual motor frequency regulation and power frequency fluctuation conditions, the shear flow field energy input can fully break down and deagglomerate the inorganic grain agglomerates within the process window of 15.0 m / s to 22.0 m / s, ensuring that the dispersion fineness reaches below 20 μm. Within this range, the emulsion particles are protected by the steric hydration protective layer and do not undergo mechanical agglomeration.
[0030] After obtaining a semi-coated slurry with an apparent dynamic viscosity between 1200 mPa·s and 2500 mPa·s, the linear velocity of the dispersion disc was rapidly reduced to 4.4 m / s, and the process was switched to a wide-blade laminar convection mixing mode for laminar homogenization. In four batches, 85 kg of sodium borosilicate hollow microspheres with a true density of 0.25 g / cm³ and an isostatic compressive strength of 14 MPa, and 25 kg of hydrophobically modified silica aerogel powder with a specific surface area of 650 m² / g were added to the reactor. The feeding time for each batch was controlled at 5 min, with a total feeding time of 20 min. An effective shear gap of 0.08 m was maintained between the edge of the dispersion impeller and the inner wall of the reactor. An online torque sensor collected the effective net torque of the dispersion shaft in real time, and the net torque power output of the dispersion shaft was calculated based on the current rotation speed. A material temperature sensor simultaneously detected the material temperature and calculated the output torque power based on the net torque power. The apparent dynamic viscosity of the slurry is calculated based on the material temperature to monitor changes in apparent dynamic viscosity in real time. When the measured apparent dynamic viscosity of the slurry exceeds 2500 mPa·s, the operating speed of the dispersion shaft is automatically reduced to 200 rpm to 250 rpm, and a set mass of deionized water is pulsed in to eliminate local high stress concentration. When the measured apparent dynamic viscosity of the slurry is below 1200 mPa·s, the interval between single batches of material is extended to 8 min to 12 min. This ensures that the maximum hydrodynamic shear stress exerted by the material on the sodium borosilicate hollow microspheres is always controlled below the safe threshold of the intrinsic failure strength of the microsphere material. After 20 min of low-stress laminar flow homogenization, the sodium borosilicate hollow microspheres are in a laminar flow suspension state and form a homogeneous suspension distribution in the slurry. The mechanical fragmentation rate of the microspheres is controlled at 0.6%, and the low thermal conductivity cavity structure of the internal sealed dry air is completely preserved.
[0031] After achieving homogeneous suspension of sodium borosilicate hollow microspheres and hydrophobically modified silica aerogel powder, an atomizing spray gun was activated and driven by compressed air at 0.5 MPa. Within 15 minutes, 35 kg of a 15 wt% methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution, along with a room-temperature latent titanium lactate chelate aqueous solution, was atomized and sprayed onto the surface of the reaction material. The average droplet size was controlled to be 10 μm to 30 μm, the material temperature was adjusted to be constant at 40 °C, and a pH adjuster was injected to control the pH of the system in the reactor to 8.5. The reaction was carried out at a constant temperature and low speed for 30 minutes with a stirring speed of 220 rpm. The silane triol groups generated by hydrolysis diffuse and migrate to the surface of inorganic particles in a weakly alkaline aqueous phase. They undergo dehydration and condensation reactions with residual inorganic hydroxyl groups on the surfaces of sodium borosilicate hollow microspheres, hydrophobically modified silica aerogel powder, and rutile titanium dioxide powder, forming a silicon-oxygen covalent network. At the other end of the molecular chain, the methacryloyloxy organic functional group undergoes an in-situ interfacial reaction with the acrylate polymer molecular chains pre-adsorbed around the particles, forming segment interpenetration and entanglement. This connects the silane hydrolysate to the surface of the inorganic filler and the polymer molecular chains, forming a nanoscale organic-inorganic hybrid crosslinking process with a covalent bond coverage of 79.01%. The coating layer reduces interfacial gaps and phase separation defects between the organic and inorganic phases, lowers thermal conductivity at the phase interface, and the composite-injected titanium lactate chelate remains chemically inert under normal temperature storage conditions. During coating application and drying, when the temperature rises to above 35°C via photothermal heating, ligand dehydration and dissociation occur, releasing coordinated titanate. The coordinated titanate undergoes a secondary polycondensation and crosslinking reaction with the carboxyl and hydroxyl groups on the polymer molecular chain, further increasing the density of the deep crosslinking network in the cured coating. Specifically, the titanium lactate chelate in the room-temperature latent type aqueous solution is selected as bis(lactic acid hydroxy diisopropyl)titanate monoammonium salt. During the atomized composite injection process, the pre- First, a 50wt% aqueous solution of dilactic acid hydroxydiisopropyl titanate monoammonium salt is homogeneously premixed with a prepared methacryloyloxypropyltrimethoxysilane prehydrolyzed solution at room temperature at a ratio of 0.3% to 0.5% of the total feed mass. In this embodiment, the amount added is 3.5 kg. The dilactic acid ligand in the chelate molecule forms a cyclic five-membered coordination chelate structure with the central titanium ion in a weakly alkaline medium at room temperature, effectively shielding the coordination hydrolysis active center of the titanium atom, so that it does not undergo early hydrolysis precipitation when mixed with the methacryloyloxypropyltrimethoxysilane prehydrolyzed solution, thus maintaining storage chemical stability.
[0032] After the interfacial covalent anchoring reaction was completed, 72 kg of a compound consisting of a hydrophobically modified ethoxylated carbamate copolymer as an associative polyurethane thickener, an antifoaming agent, and a film-forming aid was added to the reactor. The stirring speed was increased to 400 rpm and homogenized for 15 minutes. A pH adjuster was added to adjust the pH of the system to 9.2, and the viscosity was measured using a Stormer viscometer at a constant temperature of 25°C. By adjusting the amount of rheology modifier, the Stormer apparent viscosity, expressed in Krebs units (KU), was stabilized at 96 KU, within the standard application viscosity range of 85 KU to 110 KU. The hydrophobic end groups of the hydrophobically modified ethoxylated carbamate copolymer formed hydrophobic associations with the polymer layer coating the surface of the inorganic particles. The hydrophilic polyether segments extended in the aqueous phase to form a reversible three-dimensional spatial network framework, maintaining the thixotropic yield value of the material in the static storage state at a level that prevents the sodium borosilicate hollow microspheres from floating and delaminating. At the same time, it produced a shear thinning response under coating shear stress. The modified water-based heat-insulating coating composite emulsion was obtained by cooling the material, filtering it through a 200-mesh stainless steel filter, and packaging it. After curing and drying, the coating achieved a room-temperature dry film thermal conductivity of 0.034 W / (m·K), a solar full-band reflectance of 0.92, a near-infrared reflectance of 0.94, a hemispherical emissivity of 0.89, and a water absorption rate reduced to 2.1% after 168 hours of immersion in water. It withstood over 15,000 washes without any damage or exposure to the substrate. It also demonstrated excellent performance under long-term outdoor humidity, heat, and ultraviolet radiation. To maintain high solar reflectance and low thermal conductivity under aging conditions, the 72kg compound is composed of the following components: 12kg of hydrophobically modified ethoxylated urethane copolymer emulsion with a solid content of 25wt%, 4kg of polyether modified polysiloxane defoamer, 16kg of alcohol ester twelve film-forming aid, and 40kg of deionized water. After premixing and homogenizing each component at room temperature, it is added to the reactor at one time to allow the rheology thickener and film-forming aid to be rapidly and uniformly distributed in the continuous aqueous phase.
[0033] Example 2: This example uses a 1500L dispersion and preparation system with jacketed circulation temperature control and online monitoring to prepare a series of samples to investigate the effects of different process parameters, two-stage flow field stress decoupling, and in-situ interface reactions on coating performance. The system is equipped with a high-speed dispersion disk with an outer diameter of 0.30m, a wide-bladed low-speed stirring impeller, an atomizing spray gun with a pressure of 0.5MPa, and an online dynamic torque sensor with a range of 0 to 500 N·m. The online dynamic torque sensor collects the effective net torque of the dispersion shaft and calculates the net torque power output of the dispersion shaft by combining it with the rotational speed of the dispersion disk. A laser particle size analyzer with a measurement range of 0.02μm to 2000μm is used to determine the hydrodynamic particle size distribution of rutile titanium dioxide powder. A micro-confocal volumetric buoyancy method is used to determine the mechanical fragmentation rate of sodium borosilicate hollow microspheres. X-ray photoelectron spectroscopy is used to determine the covalent bonding coverage of the inorganic filler surface. The thermal conductivity of the cured coating at room temperature was determined according to GB / T10294-2008; the full-spectrum reflectance of sunlight was determined according to JG / T235-2014; the near-infrared reflectance and hemispherical emissivity were determined according to GB / T25261-2018; and the washability was determined according to GB / T9755-2014. When determining the covalent bond coverage, a slurry sample after complete interfacial polycondensation was taken and repeatedly centrifuged and washed with deionized water and tetrahydrofuran solvent to remove free unreacted monomers and other impurities. The adsorbed polymer was dried to constant weight in a vacuum drying oven at 60℃ to prepare powder samples. The binding energy spectra of each element on the sample surface were measured using X-ray photoelectron spectroscopy. Peak fitting and peak area integration were performed on the characteristic metal element spectra of silicon and filler. The covalent bond coverage was determined by the percentage of the characteristic peak area of covalently bound silicon-oxygen bonds to the total area of all bound state characteristic peaks on the filler surface. The Arrhenius kinetic reaction constant and activation energy were calibrated based on the coverage growth rate under different reaction temperature gradients.
[0034] Sample groups 1 to 3 of this invention were prepared with a total feed weight of 1000 kg. Sample group 1 was prepared under the lower limit of the process and component ratio: 360.0 kg of aqueous acrylate copolymer emulsion, 150.0 kg of rutile titanium dioxide powder, 45.0 kg of calcined kaolin micropowder, 80.0 kg of sodium borosilicate hollow microspheres, and 20.0 kg of hydrophobically modified silica aerogel powder. The high-speed dispersion linear velocity was 15.0 m / s, the low-speed laminar flow homogenization linear velocity was 3.0 m / s, the silane reaction temperature was 38℃, and the reaction time was 25 min. Sample group 2 was prepared under the median standard conditions: 380.0 kg of aqueous acrylate copolymer emulsion, 180.0 kg of rutile titanium dioxide powder, and 50.0 kg of calcined kaolin micropowder. The following components were used in this invention: 85.0 kg of sodium borosilicate hollow microspheres and 25.0 kg of hydrophobically modified silica aerogel powder were added. The high-speed dispersion linear velocity was 22.78 m / s, the low-speed laminar flow homogenization linear velocity was 4.4 m / s, the silane reaction temperature was 40℃, and the reaction time was 30 min. Sample group 3 of this invention used the upper limit of the process and component ratio: 400.0 kg of waterborne acrylate copolymer emulsion, 200.0 kg of rutile titanium dioxide powder, 55.0 kg of calcined kaolin micropowder, 90.0 kg of sodium borosilicate hollow microspheres, and 30.0 kg of hydrophobically modified silica aerogel powder were added. The high-speed dispersion linear velocity was 22.0 m / s, the low-speed laminar flow homogenization linear velocity was 6.0 m / s, the silane reaction temperature was 45℃, and the reaction time was 40 min.
[0035] After processing according to the above process, the hydrodynamic particle size of the rutile titanium dioxide powder in sample group 1 of this invention is 0.38 μm, the mechanical fragmentation rate of sodium borosilicate hollow microspheres is 0.7%, the covalent bonding coverage is 75.42%, the dry film thermal conductivity is 0.037 W / (m·K), the full-spectrum solar reflectance is 0.91, the near-infrared reflectance is 0.93, the number of washes is greater than 15,000, the water absorption rate after immersion is 2.4%, and the aging reflectance retention rate is 96.8%. The hydrodynamic particle size of the rutile titanium dioxide powder in sample group 2 of this invention is 0.25 μm, the mechanical fragmentation rate of sodium borosilicate hollow microspheres is 0.6%, the covalent bonding coverage is 79.01%, the dry film thermal conductivity is 0.034 W / (m·K), the full-spectrum solar reflectance is 0.92, the near-infrared reflectance is 0.94, and the number of washes is greater than 1500. The first sample group had 0 washes, a water absorption rate of 2.1%, and an aging reflection retention rate of 97.6% after 5000 hours of accelerated artificial aging. The third sample group had a rutile titanium dioxide powder with a hydrodynamic particle size of 0.21 μm, a sodium borosilicate hollow microsphere mechanical fragmentation rate of 0.8%, a covalent bonding coverage of 82.15%, a dry film thermal conductivity of 0.033 W / (m·K), a solar full-band reflectance of 0.93, a near-infrared reflectance of 0.94, a wash resistance greater than 15000 cycles, a water absorption rate of 1.9%, and an aging reflection retention rate of 98.1%. Among the three sample groups, the sodium borosilicate hollow microsphere mechanical fragmentation rate was between 0.6% and 0.8%, the dry film thermal conductivity was between 0.033 W / (m·K) and 0.037 W / (m·K), and the solar full-band reflectance was between 0.91 and 0.93.
[0036] Control group 1 omitted the pre-passivation step of the aqueous phase stabilizer and directly added pigments and fillers for high-speed dispersion at a high-speed dispersion linear velocity of 22.0 m / s, a low-speed homogenization linear velocity of 4.4 m / s, and a reaction temperature of 40℃. After treatment, the hydrodynamic particle size of rutile titanium dioxide powder was 0.42 μm, the mechanical fragmentation rate of sodium borosilicate hollow microspheres was 0.8%, the covalent bonding coverage was 71.20%, the dry film thermal conductivity was 0.068 W / (m·K), the full-band solar reflectance was 0.84, the near-infrared reflectance was 0.86, the number of washes was 2800, the water absorption rate after immersion was 8.5%, and the aging reflectance retention rate was 81.2%. Because the spatial steric hydration protective layer constructed by the aqueous phase stabilizer was not formed on the surface of the latex particles, the mechanical shear rate that the emulsion was subjected to under high linear velocity and strong shear exceeded the critical threshold for demulsification, resulting in local demulsification and microgel aggregation, and the continuity of the paint film decreased accordingly.
[0037] In control group 2, sodium borosilicate hollow microspheres were directly added during the high-speed dispersion stage. The entire process was sheared at a high linear velocity of 18.0 m / s, with the homogenization linear velocity also at 18.0 m / s. The reaction temperature was 40℃. After treatment, the hydrodynamic particle size of the rutile titanium dioxide powder was 0.27 μm, the mechanical fragmentation rate of the sodium borosilicate hollow microspheres was 24.8%, the covalent bonding coverage was 74.30%, the dry film thermal conductivity was 0.078 W / (m·K), the full-band solar reflectance was 0.88, the near-infrared reflectance was 0.90, the number of wash cycles was 9200, the water absorption rate after immersion was 4.6%, and the aging reflectance retention rate was 89.5%. In this high-shear flow field, the maximum hydrodynamic shear stress exerted by the material on the sodium borosilicate hollow microspheres exceeded their dynamic shear resistance safety threshold. After the microspheres were broken, the closed-cell heat-insulating air layer was wetted by the resin, and the corresponding dry film thermal conductivity increased accordingly.
[0038] Control group 3 omitted the interfacial reaction step involving the pre-hydrolyzed solution of methacryloyloxypropyltrimethoxysilane and the aqueous solution of room-temperature latent titanium lactate chelate. The high-speed dispersion linear velocity was 22.0 m / s, the homogenization linear velocity was 4.4 m / s, and the reaction temperature was 40℃. After treatment, the hydrodynamic particle size of rutile titanium dioxide powder was 0.26 μm, the mechanical fragmentation rate of sodium borosilicate hollow microspheres was 0.7%, the covalent bonding coverage was 0.00%, the dry film thermal conductivity was 0.052 W / (m·K), the full-band solar reflectance was 0.91, the near-infrared reflectance was 0.92, the number of wash cycles was 4500, the water absorption rate after immersion was 6.8%, and the aging reflectance retention rate was 84.5%. Because the interfacial polycondensation and crosslinking between the silane hydrolysate and the inorganic filler and polymer molecular chains were not carried out, the inorganic filler and the resin matrix mainly maintained a physical adsorption state. The residual gap at the interface corresponds to a higher thermal conductivity and lower wash resistance.
[0039] Control group 4 maintained a high-speed dispersion linear velocity of 22.0 m / s, a homogenization linear velocity of 4.4 m / s, and a reaction temperature of 40 °C. A pre-hydrolyzed solution of methacryloyloxypropyltrimethoxysilane was sprayed via atomization, but no room-temperature latent titanium lactate chelate aqueous solution was added. After treatment, the hydrodynamic particle size of the rutile titanium dioxide powder was 0.25 μm, the mechanical fragmentation rate of the sodium borosilicate hollow microspheres was 0.6%, the covalent bonding coverage was 78.40%, the dry film thermal conductivity was 0.035 W / (m·K), the solar reflectance across the entire wavelength range was 0.92, and the near-infrared... The reflectance was 0.93, the number of washes was 12,500, the water absorption rate was 2.5%, and the aging reflectance retention rate after 5,000 hours of accelerated artificial aging was 88.2%. Compared with sample group 2 of the present invention, which contained an aqueous solution of room temperature latent titanium lactate chelate, the aging reflectance retention rate of this group was lower. In sample group 2 of the present invention, after the titanium lactate chelate was activated by heat during film formation, the ligands underwent dehydration and dissociation, releasing coordinated titanate. The coordinated titanate underwent a secondary polycondensation and crosslinking reaction with the carboxyl and hydroxyl groups on the polymer molecular chain, which corresponds to the difference in reflectance retention performance after aging.
[0040] In control group 5, the high-speed dispersion linear velocity was reduced to 12.0 m / s, the homogenization linear velocity was 4.4 m / s, and the reaction temperature was 40℃. After treatment, the hydrodynamic particle size of the rutile titanium dioxide powder was 0.58 μm, the mechanical fragmentation rate of sodium borosilicate hollow microspheres was 0.6%, the covalent bonding coverage was 76.50%, the dry film thermal conductivity was 0.038 W / (m·K), the solar full-band reflectance was 0.82, the near-infrared reflectance was 0.83, the number of washes was greater than 15,000, the water absorption rate after immersion was 2.3%, and the aging reflectance retention rate was 95.3%. When the high-speed dispersion linear velocity was below 15.0 m / s, the fluid shear stress was insufficient to fully deagglomerate the primary agglomerates of the rutile titanium dioxide powder, resulting in an increased hydrodynamic particle size and a corresponding decrease in the solar full-band reflectance.
[0041] In control group 6, the homogenization linear velocity of sodium borosilicate hollow microspheres was increased to 8.5 m / s, the high-speed dispersion linear velocity was 22.0 m / s, and the reaction temperature was 40℃. After treatment, the hydrodynamic particle size of rutile titanium dioxide powder was 0.24 μm, the mechanical fragmentation rate of sodium borosilicate hollow microspheres was 12.6%, the covalent bonding coverage was 77.80%, the dry film thermal conductivity was 0.059 W / (m·K), the full-band solar reflectance was 0.92, the near-infrared reflectance was 0.93, the number of wash cycles was 11,000, the water absorption rate after immersion was 3.1%, and the aging reflectance retention rate was 92.4%. When the homogenization linear velocity exceeded 6.0 m / s, the flow field shear rate increased, the local hydrodynamic shear stress exceeded the safety boundary of the microspheres, the mechanical fragmentation rate of sodium borosilicate hollow microspheres increased, and the dry film thermal conductivity increased.
[0042] In control group 7, a high-speed dispersion linear velocity of 22.0 m / s, a homogenization linear velocity of 4.4 m / s, and a reaction temperature of 40 °C were maintained. The pH value of the interfacial reaction system was adjusted to 7.2. After treatment, the hydrodynamic particle size of the rutile titanium dioxide powder was 0.25 μm, the mechanical fragmentation rate of the sodium borosilicate hollow microspheres was 0.7%, the covalent bond coverage was 48.60%, the dry film thermal conductivity was 0.046 W / (m·K), the solar full-band reflectance was 0.90, the near-infrared reflectance was 0.91, the number of wash cycles was 6800, the water absorption rate after immersion was 5.2%, and the aging reflectance retention rate was 86.7%. When the pH value of the interfacial reaction system was lower than 8.2, the dehydration condensation reaction rate of silanol groups and hydroxyl groups on the particle surface decreased, and the corresponding covalent bond coverage decreased.
[0043] Control group 8 maintained a high-speed dispersion linear velocity of 22.0 m / s, a homogenization linear velocity of 4.4 m / s, and a reaction temperature of 40 °C. The final kinematic viscosity (KU) was adjusted to 70 KU. After treatment, the hydrodynamic particle size of the rutile titanium dioxide powder was 0.25 μm, the mechanical fragmentation rate of the sodium borosilicate hollow microspheres was 0.6%, the covalent bonding coverage was 78.10%, the dry film thermal conductivity was 0.043 W / (m·K), the solar full-band reflectance was 0.89, the near-infrared reflectance was 0.91, the number of washes was greater than 15,000, the water absorption rate after immersion was 2.6%, and the aging reflectance retention rate was 94.8%.
[0044] Further verification was conducted using different boundary material combinations with calcined kaolin micropowder particle sizes ranging from 1.5 μm to 2.5 μm and hydrophobically modified silica aerogel powder specific surface areas ranging from 600 m² / g to 700 m² / g. Within the above-mentioned ratios and process windows, the layered structure of calcined kaolin micropowder, the nanoporous framework of hydrophobically modified silica aerogel powder, and rutile titanium dioxide powder together form an optical scattering and microporous thermal insulation structure. The resulting cured dry film of the coating has a thermal conductivity ranging from 0.032 W / (m·K) to 0.038 W / (m·K), and the full-band solar reflectance and near-infrared reflectance both meet the corresponding index requirements. Within the fluctuation range of the above-mentioned raw material physicochemical properties, the process parameters used can still enable the coating to maintain the corresponding thermal conductivity and reflectance properties.
[0045] Example 3: In this example, water-based thermal insulation coatings were prepared on an industrial scale in a 1500L dispersion reactor equipped with a thermally conductive jacket and an online torque sensor. The control parameters for the fluid dynamics shear field and microphase reaction kinetics were calibrated throughout the entire process. First, 165kg of deionized water and 380kg of a water-based acrylate copolymer emulsion with a solid content of 50wt% and a pH of 7.5 were added. A three-bladed agitator was started and its speed was controlled at 350rpm. Circulating cooling water was introduced into the reactor jacket to stabilize the initial temperature of the material between 22°C and 25°C. Subsequently, a dripping rate of 0.8% of the total formulation mass was added per minute. 8 kg of an aqueous phase stabilizer, prepared by mixing a 40 wt% polyether-modified sodium polycarboxylate salt aqueous solution with a nonionic amphiphilic block copolymer at a mass ratio of 1:1, was injected into the reactor. The mixture was continuously stirred at low speed for 20 min. This allowed the anionic carboxylate groups to coordinate and bind to the surface of the polymer latex particles, while the nonionic polyether segments extending into the aqueous phase formed a steric hydration protective layer with a thickness of 3 nm to 8 nm. This increased the critical demulsification shear rate of the aqueous acrylate copolymer emulsion under mechanical shear from 4500 / s in the unpassivated state to over 12000 / s, providing a rheological and colloidal thermodynamic stability basis for subsequent high energy density shear conditions.
[0046] 180 kg of rutile titanium dioxide powder with an average particle size of 0.25 μm and 50 kg of calcined kaolin powder with a particle size of 1.5 μm to 2.5 μm were added sequentially to the pre-passivated resin emulsion. The ratio of the outer diameter of the dispersion disc impeller to the inner diameter of the reactor was adjusted to 0.30, and the diameter of the dispersion disc was set. The dispersion motor was started, bringing the actual operating speed of the dispersion shaft to 1450 rpm, which translates to a linear velocity of 22.78 m / s at the edge of the dispersion disk. The temperature of the slurry was controlled between 38°C and 42°C by adjusting the cooling water flow rate of the jacket to balance the shear heat generated by fluid viscosity dissipation. The slurry was continuously dispersed in a strong turbulent shear flow field for 30 minutes, allowing the hydrodynamic shear stress to overcome the van der Waals forces of the original pigment agglomerates. The slurry fineness was measured to be less than or equal to 20 μm using a scraper fineness gauge, and the hydrodynamic particle size of the rutile titanium dioxide powder was within the range of 0.2 μm to 0.4 μm. Protected by the steric hydration protective layer, the polymer latex particles penetrated into the gaps between pigment particles under the pressure difference driven by shear-induced flow, forming a preliminary hydrodynamic adsorption coating layer. The system then transformed into an apparent dynamic viscosity. The semi-coated slurry.
[0047] To ensure that the true density of the subsequently added material is 0.25 g / cm³ and the intrinsic isostatic compressive strength at break is... Sodium borosilicate hollow microspheres and hydrophobically modified silica aerogel powder with a specific surface area of 650 m² / g do not experience shell wall crushing or mesopore collapse during mixing. The operating speed of the dispersion disc is then rapidly reduced to... The corresponding linear velocity was reduced to 4.4 m / s, and a wide-blade frame impeller was switched on; the effective shear gap width between the impeller edge and the inner wall of the reactor was controlled. Four batches of sodium borosilicate hollow microspheres and 25 kg of hydrophobically modified silica aerogel powder were added, with each batch feeding time controlled at 5 min and the total feeding time at 20 min. During the laminar flow homogenization stage, the maximum hydrodynamic shear stress exerted by the medium on the sodium borosilicate hollow microspheres was measured. Safety limits of microbead destruction The mechanical control relationship is expressed as: ,in, The apparent dynamic viscosity of the slurry under the current shear conditions. The maximum shear rate in the flow field. The outer diameter of the impeller of the mixing and dispersing disc is set to 0.30m; The actual operating speed of the dispersion shaft is taken as 280 rpm; The effective shear gap between the impeller edge and the vessel wall is set to 0.08 m. The dynamic shear attenuation safety factor for the microspheres is set to 0.15. The intrinsic compressive strength of the microspheres is taken as a value. The maximum shear rate of the flow field was obtained by substituting the parameters under normal operating conditions. The maximum shear stress applied by the fluid to the microspheres Microbeads' resistance to damage safety threshold The actual maximum shear stress is lower than the safety failure threshold. During this process, the online torque sensor collects the effective net torque of the dispersion shaft in real time, and calculates the net torque power output of the dispersion shaft based on the current actual operating speed of the dispersion shaft. The temperature sensor collects the material temperature simultaneously, and calculates the apparent dynamic viscosity of the slurry based on the net torque power output of the dispersion shaft and the material temperature. When the batch fluctuation of the raw material oil absorption causes the apparent dynamic viscosity of the slurry to exceed 2500 mPa·s, the system automatically reduces the speed to 200 rpm to 250 rpm and pulses a set mass of deionized water into the high-stress area at the bottom of the vessel to eliminate local stress concentration. When the apparent dynamic viscosity is lower than 1200 mPa·s, the single batch feeding interval is automatically extended to 8 min to 12 min. During extreme working condition verification, the upper limit of the abnormal apparent dynamic viscosity of 12.0 Pa·s and the upper limit of the speed of 600 rpm are substituted to calculate the ultimate shear stress. The ratio of this value to the safety threshold is After 20 minutes of low-stress laminar flow homogenization, sodium borosilicate hollow microspheres formed a homogeneous suspension distribution in the material. The mechanical fragmentation rate of the microspheres was controlled at 0.6%, maintaining the integrity of the sealed low thermal conductivity air cavity inside the microspheres. The damage of the hollow microspheres in the flow field mainly stemmed from the concentration of fluid shear stress, leading to radial deformation and local stress yielding in the thin-walled cavity. The nominal isostatic compressive strength of the microspheres reflects the material's ultimate failure threshold under three-dimensional omnidirectional uniform hydrostatic pressure. The uniaxial shear stress applied by the flow field is transformed into the normal pressure of the spherical wall through the continuous phase boundary layer. The mechanical mapping relationship between the two is determined by the viscous drag of the medium and the bearing characteristics of the hollow spherical shell's geometric cross-section. By confining the maximum shear stress of the flow field within the calculated safety critical threshold, the instability and rupture of the microsphere shell due to local deviatoric stress concentration can be avoided.
[0048] After the adiabatic microparticles are homogeneously suspended, the atomizing spray gun is activated. Driven by compressed air at a pressure of 0.5 MPa, 35 kg of a 15 wt% methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution, along with a room-temperature latent titanium lactate chelate aqueous solution, is atomized and sprayed onto the surface of the reaction material within 15 minutes. The average atomized droplet size is controlled to be between 10 μm and 30 μm. The jacket water temperature is adjusted to keep the reaction material at a constant temperature within the thermodynamic absolute temperature range. That is, at 40℃, a pH adjuster is added to maintain the pH of the material system at 8.5, and the reaction is carried out at a constant temperature and low speed at a dispersion shaft speed of 220 rpm for a duration of [missing information]. That is, the covalent bonding coverage of silane hydrolysis products between the inorganic particle surface and the resin microdomains over 30 minutes. Following the Arrhenius equations of motion: ,in, The pre-exponential factor for the apparent kinetics of interfacial condensation polymerization is given by the following value: ; The activation energy for the dehydration condensation reaction between silanol groups and hydroxyl groups on the particle surface is given by [value]. ; Let be the molar gas constant, and take the value of . ; The absolute thermodynamic temperature of the reaction is taken as 313.15 K; This represents the concentration of the reactive coupling agent hydrolyzed monomer, with a value of 0.085 mol / L. This is the reaction order exponent, with a value of 1; The isothermal anchoring reaction time is taken as 1800 s, and substituted into the calculation of the Arrhenius reaction constant. , reaction index term Calculate the covalent bond coverage The design threshold requirement of ≥75% is met. The silane triol groups generated by hydrolysis dehydrate and condense with the inorganic hydroxyl groups on the surface of sodium borosilicate hollow microspheres, hydrophobically modified silica aerogel powder, and rutile titanium dioxide powder to form a silicon-oxygen covalent bond network. The methacryloyloxy group at the other end of the molecule undergoes an in-situ cross-linking reaction with the polymer molecular chain, so that the silane hydrolysate forms an interfacial cross-linking connection with the inorganic filler and polymer molecular chain, and forms a nanoscale hybrid cross-linking tough transition layer at the phase interface, eliminating the interfacial wetting gap and inhibiting the thermal phonon scattering and conduction at the phase interface. The lactate titanium chelate injected with it remains chemically inert under the protection of ligands under room temperature storage conditions. When the coating is applied and the film is heated to above 35°C, the ligands dehydrate and dissociate, releasing the coordinated titanate. The coordinated titanate undergoes a secondary condensation cross-linking reaction with the carboxyl and hydroxyl groups on the resin molecular chain, increasing the density of the deep cross-linking network.
[0049] After the interfacial covalent reaction was completed, 72 kg of a compound consisting of a hydrophobically modified ethoxylated urethane copolymer as an associative polyurethane thickener, an antifoaming agent, and a film-forming aid was added to the system. The stirring speed was increased to 400 rpm for homogeneous dispersion for 15 min. A pH adjuster was added to adjust the pH value of the material to 9.2, and the kinematic viscosity was stabilized at 96 KU using a Stormer viscometer. The hydrophobic end groups of the hydrophobically modified ethoxylated urethane copolymer formed hydrophobic associations with the polymer layer coated on the surface of the inorganic particles. The hydrophilic polyether segments extended in the aqueous phase to form a reversible three-dimensional spatial network framework, which improved the thixotropic yield value of the material under static storage conditions. Maintaining a state that prevents sodium borosilicate hollow microspheres from floating and stratifying, while simultaneously generating a shear thinning response under coating shear conditions, the material is cooled, discharged, filtered through a 200-mesh stainless steel filter, and packaged to obtain a modified water-based heat-insulating coating composite emulsion. After curing to form a dry paint film, the coating has a room temperature dry film thermal conductivity of 0.034 W / (m·K), a full-spectrum solar reflectance of 0.92, a near-infrared reflectance of 0.94, a hemispherical emissivity of 0.89, and a water absorption rate controlled at 2.1% after immersion in water for 168 hours. It can withstand more than 15,000 washes without exposing the substrate and causing damage. It maintains high solar reflectance and low thermal conductivity under long-term outdoor humid heat and ultraviolet aging conditions.
[0050] Example 4: This example combines Figures 1 to 2 This paper describes the resin emulsion dispersion modification process in the production of a water-based heat insulation coating, such as... Figure 1As shown, in step S1, an aqueous phase stabilizer is added to the aqueous acrylate copolymer emulsion at a drop rate of 0.5% to 1.0% of the formulation mass fraction per minute at a rotation speed of 300 rpm to 500 rpm and a temperature of 20°C to 30°C. The mixture is then stirred and passivated for 15 to 25 minutes to obtain a pre-passivated resin emulsion. In step S2, rutile titanium dioxide powder and calcined kaolin micro-powder are added to the pre-passivated resin emulsion and sheared and dispersed at an online speed of 15 m / s to 22 m / s and a temperature not exceeding 45°C for 20 to 35 minutes to obtain a semi-coated slurry with an apparent dynamic viscosity of 1200 mPa·s to 2500 mPa·s. In step S3, the linear speed is reduced to 3 m / s to... At a speed of 6 m / s, sodium borosilicate hollow microspheres and hydrophobically modified silica aerogel powder are added in batches to the semi-coated slurry, and the mixture is laminated and homogenized in the semi-coated slurry for 10 to 20 minutes. In step S4, a methacryloxypropyltrimethoxysilane pre-hydrolyzed solution is atomized and sprayed onto the homogenized material, and the reaction is carried out at a temperature of 38°C to 45°C and a pH of 8.2 to 9.0 for 25 to 40 minutes to allow the silane hydrolysate to condense and crosslink with the inorganic filler and molecular chains. In step S5, an associative polyurethane thickener and a pH adjuster are added to the reacted material to adjust the pH to 8.8 to 9.5 and the kinematic viscosity to 85 KU to 110 KU. The material is then cooled, discharged, and filtered through a 200-mesh filter.
[0051] like Figure 2 As shown, material dispersion and interfacial reaction are carried out in a dispersion reactor. Aqueous acrylate copolymer emulsion and aqueous phase stabilizer are added to the dispersion reactor to react and form a pre-passivated resin emulsion. A steric hindrance hydration protective layer is constructed on the surface of the polymer particles. Rutile titanium dioxide powder and calcined kaolin micropowder are added to the pre-passivated resin emulsion and dispersed in the dispersion reactor to form a semi-coated slurry. This allows the polymer emulsion to form a hydrodynamic adsorption coating layer on the surface of inorganic pigments and fillers. Sodium borosilicate hollow microspheres and hydrophobically modified silica aerogel are introduced into the semi-coated slurry. The powder is homogenized in a dispersion reactor to form a homogeneous suspension distribution, preserving the internal sealed heat-insulating cavity. A pre-hydrolyzed solution of methacryloyloxypropyltrimethoxysilane and an aqueous solution of room-temperature latent titanium lactate chelate are sprayed onto the homogeneous suspension material. Condensation polymerization is induced in the dispersion reactor to form an organic-inorganic hybrid crosslinking, and a nanoscale transition layer is constructed at the phase interface. An associative polyurethane thickener and regulator are added to the reaction product. The rheological state is controlled in the dispersion reactor to generate a modified waterborne heat-insulating coating composite emulsion with a three-dimensional spatial network structure.
[0052] Example 5: Addressing the rheological damping shift caused by fluctuations in the oil absorption and solid content of raw materials during industrial batch production, this example utilizes online torque monitoring in a 1500L dispersion reactor to control the stirring speed and viscosity in real time. After adding an aqueous acrylate copolymer emulsion and an aqueous phase stabilizer for interface pre-passivation, the dispersion shaft is controlled to operate under no-load convection at 350 rpm and a constant temperature of 25°C for 5 minutes. The online torque sensor collects the effective net torque of the dispersion shaft, and the initial reference net torque power is calculated by combining it with the actual operating speed of the dispersion shaft, using this as a zero-point reference. Subsequently, rutile titanium dioxide powder and calcined kaolin micro-powder are added to form a semi-coated slurry. The online torque sensor collects the dispersion... The effective net torque transmitted from the shaft to the slurry medium is used to calculate the net power consumption for fluid stirring, combined with the actual operating speed of the motor. The immersion temperature sensor synchronously collects the slurry temperature and corrects the base viscosity of the continuous phase medium through a temperature viscosity compensation coefficient. The system control unit pre-stores the power number and Reynolds number calibration curves of agitator blades with specific geometric configurations under different flow states. Based on the measured net power consumption, speed, dispersion disk diameter, and reactor inner diameter, the stirring Reynolds number of the current flow field is calculated. Then, based on the shear stress response relationship of non-Newtonian fluids at corresponding shear rates, the apparent dynamic viscosity of the slurry is reverse-calculated through an interpolation algorithm, realizing online continuous monitoring of the viscosity state of the flow field and closed-loop speed regulation.
[0053] When the batch filler is detected to have excessive oil absorption, causing the apparent dynamic viscosity of the material to rise and exceed 2500 mPa·s, the control system automatically reduces the power supply frequency of the stirring motor, limiting the speed of the dispersion shaft to the range of 200 rpm to 250 rpm. At the same time, the quantitative metering pump is linked to pulsely inject deionized water equivalent to 0.5% to 1.0% of the total formula mass into the high flow rate zone at the bottom of the reactor to eliminate the local high shear stress accumulation zone. This ensures that the maximum hydrodynamic shear stress in the low stress homogenization stage is lower than the breakage safety limit of sodium borosilicate hollow microspheres, maintaining the mechanical fragmentation rate of the microspheres at less than or equal to 0.8%, and preserving the integrity of the internal sealed air heat-insulating cavity.
[0054] For outdoor high-temperature and high-humidity service conditions, a room-temperature latent titanium lactate chelate is introduced into the system. This titanium lactate chelate remains chemically inert under the protection of ligands in a room-temperature aqueous weakly alkaline medium. After the finished coating is filtered through a 200-mesh filter, it does not undergo self-condensation reaction during 12 months of sealed storage at 5℃ to 30℃. The kinematic viscosity, expressed in KU, remains between 85KU and 110KU. When the coating is sprayed onto the substrate surface and the local temperature of the coating reaches above 35℃ under natural sunlight, the chelate ligands undergo dehydration and dissociation upon heating, releasing coordinated titanate. The coordinated titanate undergoes secondary condensation crosslinking with the residual carboxyl and hydroxyl groups on the resin molecular chain and the hydroxyl groups on the surface of the inorganic filler, forming a titanium-oxygen crosslinking network inside the dry film, which increases the three-dimensional network crosslinking density of the cured coating. After 5000 hours of artificial accelerated aging test, the reflectance of the coating across the entire wavelength band is still greater than or equal to 0.91, and the thermal conductivity of the dry film is less than or equal to 0.038W / (m·K).
[0055] In the early stage of film formation, moisture continuously evaporates from the surface of the paint film. Volatile neutralizing amines in the system evaporate with the water vapor, and the micro-environment of the paint film gradually shifts from weakly alkaline to neutral. At the same time, the matrix solid content increases and the intermolecular distance decreases. When the coating is exposed to sunlight and the local surface temperature rises above 35°C, free water molecules desorb and the dielectric constant decreases. The thermodynamic dynamic equilibrium of the coordination five-membered ring shifts towards ligand exchange. Under the driving force of dehydration and the transfer of neutralized protons, the dilactic acid ligand dissociates and releases coordinated titanate. The coordinated titanate further undergoes coordination condensation with the carboxyl and hydroxyl groups of the polymer side chain and the hydroxyl groups on the filler surface to form a dense titanium-oxygen covalent network.
[0056] Example 6: This example addresses the differences in initial charge density between different batches of waterborne polymer emulsions in a waterborne thermal insulation coating production line, as well as the anti-buoyancy storage stability requirements of lightweight hollow thermal insulation fillers. Material interface pre-passivation and colloidal rheological network adjustment were performed in a 1500L dispersion reactor. First, 165 kg of deionized water and 380 kg of a waterborne acrylate copolymer emulsion with a solid content of 50 wt% and a pH of 7.5 were injected into the reactor. The jacket cooling water was turned on, the stirring speed was set to 350 rpm, and the material temperature was maintained at 25°C. Using a constant flow metering pump, an aqueous phase stabilizer prepared by compounding a 40 wt% polyether-modified sodium polycarboxylate aqueous solution and a nonionic amphiphilic block copolymer at a mass ratio of 1:1 was injected into the system at a constant rate of 0.8% (8 kg / min) of the total formulation mass. The system was continuously stirred and passivated for 20 minutes. During the dropwise addition process, the hydrophobic segments of the nonionic copolymer molecules and the hydrophobic backbone of the polycarboxylic acid molecules adsorb onto the surface of the polymer latex particles through hydrophobic association. The extended hydrophilic polyether segments construct a steric hindrance hydration protective layer with a thickness of 5.2 nm around the particles. A coaxial double-cylinder rotating high shear rheometer was used to continuously scan and detect the shear rate at a constant temperature of 25℃. When the emulsion undergoes a phase transition, the critical shear rate for demulsification significantly increased from 4500 / s without the addition of stabilizer to 14200 / s. Subsequently, a high-speed dispersion disk was used to strongly shear disperse 180 kg of rutile titanium dioxide powder and 50 kg of calcined kaolin micro powder at a rotation speed of 1450 rpm and a linear velocity of 22.78 m / s for 30 min to obtain a semi-coated slurry with a fineness of less than or equal to 20 μm and an apparent dynamic viscosity of 1850 mPa·s.
[0057] When determining the thickness of the steric hydration protective layer, the emulsion samples before and after passivation were diluted to a mass fraction of 0.1%. The hydrodynamic diameter distribution of polymer latex particles was measured at 25℃ using a dynamic light scattering nanoparticle size analyzer. Half of the difference between the average hydrodynamic particle size after passivation and the initial average particle size of the unpassivated pure emulsion was taken as the thickness of the steric hydration protective layer on one side. The measured thickness was 5.2 nm, which is in the range of 3 nm to 8 nm. When determining the critical shear rate for demulsification, a coaxial double-cylinder high-shear rheometer was used. The emulsion was subjected to linearly increasing shear scans from 1,000 times per second to 20,000 times per second under constant temperature of 25℃. The apparent viscosity of the system was continuously monitored. When the apparent viscosity jumped and an irreversible gel phase transition occurred, the shear rate at the corresponding inflection point was taken as the critical shear rate for demulsification. The measured value was 14,200 times per second.
[0058] After low-speed laminar flow homogenization of 85 kg of sodium borosilicate hollow microspheres and 25 kg of hydrophobically modified silica aerogel powder, and in-situ interfacial polycondensation reaction involving a pre-hydrolyzed solution of methacryloyloxypropyltrimethoxysilane and an aqueous solution of a room-temperature latent titanium lactate chelate, 72 kg of a compound consisting of a hydrophobically modified ethoxylated carbamate copolymer as an associative polyurethane thickener, an antifoaming agent, and a film-forming aid was added to the reactor. The mixture was dispersed and homogenized at 400 rpm for 15 min. The pH of the material was then adjusted to 9.2 by adding a pH adjuster. The hydrophobic end groups of the hydrophobically modified ethoxylated carbamate copolymer formed hydrophobic associations with the polymer layer coated on the surface of the inorganic filler, and the hydrophilic polyether segments extended in the aqueous phase to form a reversible three-dimensional network. The apparent viscosity, measured using a Stormer viscometer and expressed in Krebs units (KU), reached 96 KU. Within the standard process range of 85KU to 110KU, rheometer measurements show that the rheological network generates a static thixotropic yield value greater than or equal to 1.8 Pa under static conditions, which is used to balance the upward migration stress caused by buoyancy in sodium borosilicate hollow microspheres with a true density of 0.25 g / cm³. Under the high shear rate of construction spraying, the system produces a shear thinning response, the material cools down and is discharged, and mechanical impurities are filtered out through a 200-mesh stainless steel filter, resulting in a modified water-based thermal insulation coating composite emulsion that does not delaminate or harden after 12 months of storage. After curing and film formation, the thermal conductivity of the dry film at room temperature reaches 0.034 W / (m·K), the full-band solar reflectance reaches 0.92, the near-infrared reflectance reaches 0.94, the hemispherical emissivity reaches 0.89, the water absorption rate of the paint film is controlled at 2.1% after immersion in water for 168 hours, and the number of washes exceeds 15,000 without any exposure or damage to the substrate.
[0059] The above description is only a few preferred embodiments of the present invention and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the embodiments of the present invention is not limited to the technical solutions formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the above-mentioned inventive concept. For example, technical solutions formed by replacing the above-mentioned features with, but not limited to, the technical features disclosed in the embodiments of the present invention that have similar functions.
Claims
1. A resin emulsion dispersion modification process in the production of water-based thermal insulation coatings, characterized in that, Includes the following steps: Step S1: Add an aqueous phase stabilizer to the aqueous acrylate copolymer emulsion at a speed of 300 rpm to 500 rpm and a temperature of 20°C to 30°C at a dropping rate of 0.5% to 1.0% of the formulation mass fraction per minute, and stir and passivate for 15 min to 25 min to obtain a pre-passivated resin emulsion. Step S2: Add rutile titanium dioxide powder and calcined kaolin micro powder to the pre-passivated resin emulsion, and shear and disperse them online at a speed of 15 m / s to 22 m / s and a temperature not exceeding 45°C for 20 min to 35 min to obtain a semi-coated slurry with an apparent dynamic viscosity of 1200 mPa·s to 2500 mPa·s. Step S3: Reduce the linear velocity to 3 m / s to 6 m / s, add sodium borosilicate hollow microspheres and hydrophobic modified silica aerogel powder to the semi-coated slurry in batches, and homogenize in the semi-coated slurry in laminar flow for 10 min to 20 min. Step S4: A pre-hydrolyzed solution of methacryloyloxypropyltrimethoxysilane is atomized and sprayed into the homogenized material. The reaction is carried out at a temperature of 38°C to 45°C and a pH of 8.2 to 9.0 for 25 min to 40 min, so that the silane hydrolysate and inorganic filler and molecular chain are polycondensed and crosslinked. Step S5: Add an associative polyurethane thickener and a pH adjuster to the reacted material to adjust the pH value to 8.8 to 9.5 and the kinematic viscosity to 85 KU to 110 KU. Cool the material and discharge it through a 200-mesh filter.
2. The resin emulsion dispersion modification process in the production of water-based thermal insulation coatings according to claim 1, characterized in that, Based on a total feed weight of 1000 kg, the feed weight of the waterborne acrylic copolymer emulsion is 360.0 kg to 400.0 kg with a solid content of 45 wt% to 55 wt%; the feed weight of the rutile titanium dioxide powder is 150.0 kg to 200.0 kg with an average particle size of 0.19 μm to 0.29 μm; the feed weight of the calcined kaolin micro powder is 45.0 kg to 55.0 kg with a particle size of 1.5 μm to 2.5 μm; the feed weight of the sodium borosilicate hollow microspheres is 80.0 kg to 90.0 kg with a true density of 0.15 g / cm³ to 0.35 g / cm³ and an isostatic compressive strength of 12 MPa to 18 MPa; and the feed weight of the hydrophobically modified silica aerogel powder is 20.0 kg to 30.0 kg with a specific surface area of 600 m² / g to 700 m² / g.
3. The resin emulsion dispersion modification process in the production of water-based thermal insulation coatings according to claim 1, characterized in that, Step S1 includes the following sub-steps: Step S11, a 40wt% solid content aqueous solution of polyether-modified sodium polycarboxylate salt is compounded with a nonionic amphiphilic block copolymer containing polyoxyethylene and polyoxypropylene blocks at a mass ratio of 1:1 to form an aqueous phase stabilizer; Step S12, the aqueous phase stabilizer is added dropwise to the aqueous acrylate copolymer emulsion at a rotation speed of 300 rpm to 500 rpm.
4. The resin emulsion dispersion modification process in the production of water-based heat-insulating coatings according to claim 1, characterized in that, Step S2 includes the following sub-steps: Step S21, controlling the ratio of the outer diameter of the dispersion disc impeller to the inner diameter of the dispersion reactor to be 0.25 to 0.35, circulating cooling water into the jacket of the outer wall of the dispersion reactor to maintain the material temperature in the range of 38℃ to 42℃; Step S22, forcefully shearing and dispersing rutile titanium dioxide powder and calcined kaolin micro powder at a dispersion disc linear velocity of 15m / s to 22m / s, stopping the high-speed shearing when the slurry dispersion fineness is less than or equal to 20μm and the hydrodynamic particle size of the rutile titanium dioxide powder is in the range of 0.2μm to 0.4μm, as detected by a scraper fineness gauge.
5. The resin emulsion dispersion modification process in the production of water-based thermal insulation coatings according to claim 1, characterized in that, Step S4 includes the following sub-steps: Step S41, a 15wt% methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution is introduced into an atomization system and sprayed onto the material surface by atomizing spray gun driven by compressed air at a pressure of 0.5MPa, controlling the average atomized droplet size to be 10μm to 30μm; Step S42, the reaction is carried out at a constant temperature of 200rpm to 240rpm and a material temperature of 38℃ to 45℃ for 25min to 40min, so that the covalent bonding coverage of the silane hydrolysis product between the inorganic particle surface and the resin microregion reaches more than 75%.
6. The resin emulsion dispersion modification process in the production of water-based thermal insulation coatings according to claim 1, characterized in that, In step S4, the pre-hydrolyzed solution of methacryloyloxypropyltrimethoxysilane is injected into an aqueous solution of a room-temperature latent titanium lactate chelate.
7. The resin emulsion dispersion modification process in the production of water-based thermal insulation coatings according to claim 1, characterized in that, In step S3, the online torque sensor and material temperature sensor configured in the dispersion reactor are used to detect the net torque power output of the dispersion shaft and the material temperature in real time, and include the following control sub-steps: Step S31, when the apparent dynamic viscosity of the slurry exceeds 2500 mPa·s, the working speed of the dispersion shaft is reduced to 200 rpm to 250 rpm, and deionized water is injected into the dispersion reactor to bring the apparent dynamic viscosity back to the range of 1200 mPa·s to 2500 mPa·s; Step S32, when the apparent dynamic viscosity of the slurry is lower than 1200 mPa·s, the interval time between single batch feeding is extended to 8 min to 12 min to maintain the laminar suspension state of the flow field.
8. The resin emulsion dispersion modification process in the production of water-based thermal insulation coatings according to claim 1, characterized in that, Step S5 includes the following sub-steps: Step S51, adding a hydrophobically modified ethoxylated urethane copolymer as an associative polyurethane thickener to the reacted material; Step S52, adding a pH adjuster to adjust the pH of the system to 8.8 to 9.
5.
9. The resin emulsion dispersion modification process in the production of water-based thermal insulation coatings according to claim 1, characterized in that, After the water-based heat-insulating coating prepared by the process is dried, the thermal conductivity of the dry film at room temperature is 0.032 W / (m·K) to 0.038 W / (m·K), the reflectance of the full spectrum of sunlight is greater than or equal to 0.91, the reflectance of the near-infrared spectrum is greater than or equal to 0.93, the hemispherical emissivity is greater than or equal to 0.88, the water absorption rate of the film after immersion in water for 168 hours is less than or equal to 2.5%, and the film can withstand more than 15,000 washes without exposing the substrate.
Citation Information
Patent Citations
Waterproof reflective thermal insulation coating and preparation method thereof
CN113717601A
